Analysis of vacuum negative pressure therapy and traditional Chinese medicine lavage in combination with tadalafil for vascular erectile dysfunction - Liang, Ke; Ke, Zunjin; Huang, Jianhong; Fei, Xiang; Qi, Liang; Wang, Jie (Frontiers in Reproductive Health, 2024)
This study investigates the clinical effects of the novel Traditional Chinese Medicine (TCM) topical wash used in combination with negative pressure irrigation and tadalafil for the treatment of vascular erectile dysfunction. Eighty-seven patients with vascular erectile dysfunction were divided into an observation group and a control group. The observation group was administered negative pressure irrigation (TCM) in combination with oral tadalafil for four weeks, and the control group was administered oral tadalafil for four weeks. The observation group included 21 patients with arterial erectile dysfunction and 22 with intravenous erectile dysfunction. After treatment, IIEF-5, EHS, GAD scores, PSV, EDV and RI in observation group were improved compared with those before treatment (P=0.000, 0.000, 0.000, L0.000/R0.000, L0.000/R0.000, L0.003/R0.000). Erectile function (IIEF-5, EHS) was significantly improved compared with the control group (P=0.008, 0.002). In the observation group, there were 21 cases of arterial erectile dysfunction and 22 cases of intravenous erectile dysfunction. After treatment, PSV of arterial ED improved significantly (P= L0.000/R0.000), but EDV did not decrease significantly (P=L0.084/R 0.098). In patients with venous ED, PSV increased (P=L0.026/R0.032) and EDV decreased significantly (P=L0.000/R0.000). These findings suggest that TCM negative pressure lavage combined with tadalafil improves the blood supply of the penile artery, relaxes smooth muscle, and improves the closing mechanism of venous vessels in patients with vascular erectile dysfunction, ultimately improving the erectile function.